Advanced Materials for Energy Applications: From Fuels to Batteries and Beyond - Zhao Ding; Liangjuan Gao; Shicong Yang (Molecules)
The unprecedented challenges of the 21st century energy landscape necessitate a paradigm shift in materials science and engineering [...]